2017
DOI: 10.1536/ihj.16-477
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Normal Free Triiodothyronine Level Is Associated with Adverse Prognosis in Euthyroid Patients with Heart Failure Receiving Cardiac Resynchronization Therapy

Abstract: SummaryThyroid dysfunction is prevalent in patients with heart failure (HF) and hypothyroidism is related to the adverse prognosis of HF subjects receiving cardiac resynchronization therapy (CRT). We aim to investigate whether low-normal free triiodothyronine (fT3) level is related to CRT response and the prognosis of euthyroid patients with HF after CRT implantation.One hundred and thirteen euthyroid patients who received CRT therapy without previous thyroid disease and any treatment affecting thyroid hormone… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Hypothyroidism is associated with a higher mortality rate, cardiovascular events, and progression of chronic kidney disease and diabetes 1, 2, 10, 17-19 . Similarly, Chen's study found that a low-normal free triiodothyronine level was associated with HF rehospitalization and overall mortality in euthyroid patients with HF receiving CRT 20 . Not surprisingly, our patients with hypothyroidism had higher allcause mortality than those with euthyroidism despite CRT, an indication that survival is substantially associated with systemic diseases and comorbidities in HF.…”
Section: Hypothyroidism and Crt Outcomesmentioning
confidence: 88%
“…Hypothyroidism is associated with a higher mortality rate, cardiovascular events, and progression of chronic kidney disease and diabetes 1, 2, 10, 17-19 . Similarly, Chen's study found that a low-normal free triiodothyronine level was associated with HF rehospitalization and overall mortality in euthyroid patients with HF receiving CRT 20 . Not surprisingly, our patients with hypothyroidism had higher allcause mortality than those with euthyroidism despite CRT, an indication that survival is substantially associated with systemic diseases and comorbidities in HF.…”
Section: Hypothyroidism and Crt Outcomesmentioning
confidence: 88%
“…Hypothyroidism is associated with a higher mortality rate, cardiovascular events, and progression of chronic kidney disease and diabetes 1,2,10,[17][18][19] . Similarly, Chen's study found that a low-normal free triiodothyronine level was associated with HF rehospitalization and overall mortality in euthyroid patients with HF receiving CRT 20 . In contrast, similar risk of all-cause mortality was found in our patients with hypothyroidism or euthyordism.…”
Section: Hypothyroidism and Crt Outcomesmentioning
confidence: 88%
“…Hypothyroidism is associated with a higher mortality rate, cardiovascular events, and progression of chronic kidney disease and diabetes [ 1 , 2 , 10 , 17 19 ]. Similarly, Chen’s study found that a low-normal free triiodothyronine level was associated with HF rehospitalization and overall mortality in euthyroid patients with HF receiving CRT [ 20 ]. In contrast, similar risk of all-cause mortality was found in our patients with hypothyroidism or euthyordism.…”
Section: Discussionmentioning
confidence: 99%